Effective Ankaferd Hemostat Treatment For Severe Intractable Chronic Deep Leg Ulcer Associated With Behçet’s Disease - Rafiye ÇİFTÇİLER and Erdinç ÇİFTÇİLER and; him HAZNEDAROĞLU (Archives of Rheumatology, 2019)
Ankaferd hemostat (Ankaferd Blood Stopper; ABS) is a pro-hemostatic agent affecting erythrocytes. In this article, we report a 50-year-old male patient who presented with a non-healing leg ulcer for one year. He had a past medical history of Behçet’s disease (BD) diagnosed at the age of 29 and therapy was started. Patient’s leg ulcer did not respond to any treatment. Topical ABS was applied to the patient’s leg ulcer daily. Our experience suggested that local treatment of ABS can be a potentially successful therapy for the management of intractable or incurable chronic ulcers in patients with BD or for other ischemic or vasculitic skin problems.